Cullet In The Circular Economy Of The Glass Industry - Maulid Purnawan, S.Si.; Ria Julyana Manullang; Kristanto Wahyudi (Jurnal Keramik dan Gelas Indonesia, 2020)
Glass waste (cullet) in Indonesia has economic value which is currently not yet properly processed. Cullet processing could be a solution to imported cullets substitution as raw materials for the glass industry and also a solution to environmental problems. One method of processing cullets is through the circular economy. Circular economy is a model that aims to use resources effectively and efficiently by eliminating the emergence of waste and extending the functions and benefits of a resource in a production process. In this paper, a circular economy model for the glass industry has been developed which focuses on the management of cullets through the process of reduce, reuse, recycle and regenerative into cullets as glass raw materials. Several ways to help the application of a circular economy of glass waste in Indonesia are the availability of indutries that collecting, sorting and processing glass waste and also the changes of society culture in waste disposal so that glass waste does not mix with other waste and easy to recycle. Government support as policy makers can also encourage the transition process towards a circular economy.